The association between rapid growth and lipid profile: a systematic review and meta-analysis - Chen, Botian; Chen, Yunli; Wang, Yuyang; Xin, Qinghua; Ma, Defu (Frontiers in Endocrinology, 2024)
Background & aims: Metabolic disease prevalence has increased in many in many regions, and is closely associated with dyslipidemia. Rapid growth refers to a significant increase in growth velocity above the normal range, particularly in infants and children, and is highly prevalent in congenital deficiency infants. But the association between dyslipidemia and rapid growth remains controversial. We performed this meta-analysis to investigate the lipid profile in subjects with and without postnatal rapid growth, and to determine what are the confounding factors. Methods: Medline, EMBASE, China National Knowledge Infrastructure Chinese citation database and WANFANG database were searched (last search in May 2021).Publication bias was examined by constructing funnel plots, Egger's linear regression test and Begg's rank correlation test. Results: The fixed effects model would be adopted if I 2 is less than 25%, otherwise random effects model would be used. There were 11 articles involved with a total of 1148 participants (539 boys and 609 girls, mean age=7.4 years). Pooled analysis found that rapid growth was negatively associated with high-density lipoprotein cholesterol (HDL-C) (weighted mean difference=-0.068, 95%CI [-0.117, -0.020]), but not associated with triglycerides (TG), total cholesterol (TC), or low-density lipoprotein cholesterol (LDL-C). Stratified analysis suggested that increased TG were found in rapid growth subjects from developing countries. Higher TC was observed for rapid growth participants of follow-up age ≤8 years old, rapid growth duration ≤2 years, preterm, low birth weight, and from developing countries. But decreased TC was observed in small for gestational age (SGA) rapid growth subjects. Decreased LDL-C had been documented in rapid growth subjects of follow-up age >8 years old, from developed countries, and SGA. At last, rapid growth groups had lower HDL-C in infants of rapid growth duration >2 years and from developed countries. Conclusion: Rapid growth is associated with lipid profiles, particularly during early childhood, and this relationship is influenced by factors such as the duration of growth, the level of national Aims: To investigate the lipid profile in subjects with and without rapid growth, including triglyceride (TG), total cholesterol (TC), low density lipoprotein (LDL), and high density lipoprotein (HDL).